Joseph Maréchal’s interpretation of the “clear vision of God” in the mystic doctrine of Thomas Aquinas - Bańka, Aleksander R. (Folia Philosophica, 2011)
Joseph Maréchal, Belgian mysticism scholar, broadly recognized for his contribution to transcendental Thomism and acclaimed as the greatest systematician of the mystic concept of clear vision of God, raised the question on the possibility of seeing the essence of God during earthly life. According to Maréchal, Aquinas, on the ground provided by Augustine, Pseudo-Dionysius the Areopagite and other Christian authors, takes this kind of vision as a special kind of intellectual intuition strengthened by the influence of God’s light and made possible (even if, unlike the case of visio beatifica, incomplete) admiration gone in man’s soul. What is then the nature of this clear vision? What makes it different from other kinds of mystic experience? To answer these question is the aim of the paper.